Evaluation of bait traps for Tribolium confusum J. du Val (Coleoptera Tenebrionidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
The efficacy of 7 traps currently on the market was evaluated on Tribolium confusum J. du Val. Three series of tests were carried out using a one way olfactometer to evaluate the attractiveness of foods and efficiency of commercial traps. The latter were also tested in an arena. The test was carried out in a thermostatically controlled room, at 27±1°C and 70±5% r.h .. Four replications werecarried out for each test.The results confinn that the efficiency of traps depend not only on the attractant used but also on the structure and means of capture. All the traps prove to be more efficient when they are baited with soft wheat flour previously infested by T. confusum, while the commercial attractants tested are shown to be of little efficacy, particularly when the traps are placed in poorly aired environments. The most suitable trap proved to be one rectangular in shape with both base and lid in black plastic, which allows the flour beetles to enter from the 4 sides. The adhesive cardboard, used in the tested sticky traps, didn't prove to be suitable for the capture of T. confusum. In fact fewer individuals were caught compared to those attracted by the same substrates placed on filter paper. Traps with seed oil in a plastic pitfall in the middle are attractive and efficient in aiding capture.On the whole, this test shows the need to improve, by means of further research, the features of the traps currently on the market and to increase their ability to attract.
Keywords: Tribolium confusum; commercial traps; activity; olfactometer; arena